Synthesis and structural characterization of the first neptunium based metal–organic frameworks incorporating Np6O8 hexanuclear clusters. Issue 51 (24th May 2018) - Martin, N. P.; März, J.; Feuchter, H.; Duval, S.; Roussel, P.; Henry, N.; Ikeda-Ohno, A.; Loiseau, T.; Volkringer, C.
Abstract : The synthesis of the first transuranium Metal–Organic Frameworks (TRU-MOFs) is reported here. Abstract : Successful synthesis of the first transuranium metal–organic frameworks (TRU-MOFs) involving tetravalent Np 4+ is reported. These compounds were obtained from the controlled hydrolysis of Np 4+ in the presence of dicarboxylate ligands. The final structures contain the [Np6 O4 (OH)4 (H2 O)6 ] 12+ unit, which were never crystallized before with tetravalent neptunium, associated with ditopic ligands.